Method for preparing nitrile compound through oxidative cracking of nitrogen-containing compound
By oxidizing and cracking the carbon-nitrogen bonds of nitrogen-containing compounds under the action of nitrogen-doped microporous carbon-supported zinc-based catalysts, the problems of limited reactivity and environmental pollution in the preparation of nitrile compounds in the prior art are solved, and efficient, low-cost and environmentally friendly preparation of nitrile compounds are achieved.
Patent Information
- Application Number
- CN202311267315.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-28
- Publication Date
- 2025-03-28
AI Technical Summary
The prior art has problems such as limited reactivity, poor atomic economy, poor reaction conditions, poor functional group tolerance and environmental pollution when preparing nitrile compounds.
Nitrogen-containing compounds are used as substrates and oxygen as oxygen source to form nitrile compounds by oxidation cracking of carbon-nitrogen bonds (C-N) under the action of nitrogen-doped microporous carbon-supported zinc-based catalysts. The method includes adding nitrogen-containing compounds, ammonia sources, nitrogen-doped zinc-based catalysts and solvents to the reaction tubes, and passing oxygen source gas into the autoclave, and placing them in an oil bath pot to react.
It has achieved efficient and low-cost preparation of nitrile compounds, high catalyst activity, recyclable catalyst, wide range of substrates, cheap, green and rich oxygen used, and no pollution to the environment.
Smart Images

Figure BDA0004474594670000071 
Figure BDA0004474594670000081 
Figure BDA0004474594670000091
Abstract
Description
Technical Field
[0001] The invention relates to the field of chemistry and chemical engineering, and in particular to a method for preparing nitrile compounds by oxidizing and breaking carbon-nitrogen bonds (CN) of nitrogen-containing compounds. Background Art
[0002] Nitriles are important and versatile intermediates in synthetic organic chemistry and can be converted into various functional groups such as amines, ketones, amides, amines, carboxylic acids, esters, N-heterocycles, etc. In addition, nitriles are useful building blocks for dyes, natural products, herbicides, and agrochemicals. Typical routes to prepare nitriles have low atom economy, limited selectivity, and require toxic reagents. Common laboratory synthetic methods include the Sandmeyer reaction, cyanation of alkyl or aryl halides, dehydration of amide / aldehyde groups, and metal-catalyzed cyanation / cyanomethylation. In contrast, industrial synthesis usually relies on amide oxidation protocols operating at high temperatures (300-550°C). However, the above methods have some disadvantages, such as limited reactivity, poor atom economy, harsh reaction conditions, poor functional group tolerance, excessive oxidants leading to large amounts of waste emissions, and the use of toxic metal ions causing environmental pollution.
[0003] Therefore, it is worthwhile to develop a new highly active heterogeneous catalyst system for efficiently synthesizing nitrile compounds. The present invention aims to develop a method for preparing nitrile compounds by catalyzing the oxidative cleavage of the carbon-nitrogen bond of nitrogen-containing compounds, which can realize the synthesis of aromatic, heterocyclic and aliphatic nitriles, and has good selectivity, high yield, no pollution to the environment, environmental protection, economy, and industrial application prospects. Summary of the invention
[0004] The invention provides a novel method for preparing nitrile compounds. The method uses a nitrogen-containing compound as a substrate and oxygen as an oxygen source. Under the action of a catalyst, the nitrogen-containing compound undergoes oxidative cracking to generate nitrile compounds. The substrate has wide applicability and the catalyst can be recycled.
[0005] The technical solution adopted by the present invention is:
[0006] 1. A method for preparing nitrile compounds by cracking nitrogen-containing compounds, characterized in that: a nitrogen-containing compound, an ammonia source, a nitrogen-doped microporous carbon-supported zinc-based catalyst and a solvent are added to a reaction tube, then transferred to a high-pressure reactor, an oxygen source gas of 0.2-2.0 MPa is introduced, and the reactor is placed in an oil bath pot at 100-180° C. for reaction for 4-50 hours, so that the carbon-nitrogen bond (CN) can be oxidized and broken to generate the corresponding nitrile compounds.
[0007] 2. In the above technical scheme, the preparation process of the nitrogen-doped microporous carbon-supported zinc-based catalyst is as follows: 2-5g chitosan (preferably 3-4g) and 4-8g zinc chloride (preferably 6-7g) are dissolved in 100mL 5-10wt% acetic acid aqueous solution, and stirred at room temperature to form a uniform paste solution; the solution is poured into a culture dish, and dried in an oven at 80-100°C overnight to obtain a dry solid; the solid is ground into powder, and then calcined in a N2 atmosphere at a target temperature (800-1000°C) for more than 2 hours (the heating rate from room temperature to 800-1000°C is 2-5°C min -1 ); after calcination and cooling to room temperature, the resulting black powder is the target catalyst Zn-NC.
[0008] 3. In the above technical solution: the catalyst Zn-NC can be used directly without further treatment; wherein the mass content of Zn is 0.5-2wt%, and the mass content of N is 1-5wt%.
[0009] 4. In the above technical solution: in the benzylamine compound molecule, the benzene ring has one or more of the following substituents: phenyl, naphthyl, thiophene ring, pyridine ring.
[0010] The other substituents on the benzene ring are one or more of -CH3, -OCH3, -C(CH3)3, -F, -Cl, -Br, -CF3;
[0011] In the compounds containing other substituents on the benzene ring, the positions of the other substituents are para, meta or ortho;
[0012] In the nitrogen-containing compound having other substituents on the benzene ring, the number of the other substituents is 1, 2, 3 or 4.
[0013] 5. In the above technical solution: based on the molar number of Zn, the molar ratio of the added amount of the catalyst to the nitrogen-containing reaction substrate is 0.01-0.05, preferably 0.04-0.05.
[0014] 6. In the above technical scheme: the solvent is one or more of 1,4-dioxane, N,N-dimethylformamide (DMF), dimethyl sulfoxide (DMSO), 1,2-dichloroethane, toluene, acetonitrile, n-heptane, and methanol, and the amount used is 1-4 mL, preferably 2-3 mL, for every 0.25 mmol of nitrogen-containing compound.
[0015] 7. In the above technical scheme: the ammonia source is an alkaline inorganic compound, including one or more of ammonia water, ammonium carbonate, ammonium bicarbonate, ammonium oxalate, ammonium chloride, ammonium sulfate, and ammonium acetate; the molar ratio of the added amount of the ammonia source to the nitrogen-containing reaction substrate is 1-6, preferably 4-5.
[0016] 8. In the above technical solution: the oxygen source gas used is one or both of pure oxygen and air; the pressure of the oxygen source gas used is 0.2-2.0 MPa, preferably 1.0-1.5 MPa.
[0017] 11. In the above technical solution: the reaction temperature is 100-180°C, preferably 130-160°C; the reaction time is 4-50h, preferably 12-24h. It can be used directly without further treatment. The mass content of Zn is 0.5-2wt%, and the mass content of N is 1-5wt%.
[0018] The system described in the present invention can prepare nitrile compounds efficiently and at low cost, has high catalyst activity, is recyclable, has a wide substrate range, uses cheap, green and abundant oxygen, and is pollution-free to the environment, and is of great significance to the catalytic oxidation method for developing a green economy. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 The figure is a scanning electron microscope (SEM) image of the nitrogen-doped microporous carbon-supported zinc-based catalyst prepared as described below.
[0020] Figure 2 This is a transmission electron microscope (TEM) image of the nitrogen-doped microporous carbon-supported zinc-based catalyst prepared as described below. DETAILED DESCRIPTION
[0021] The following examples will help to understand the present invention, but the present invention is not limited thereto.
[0022] The preparation method of the nitrogen-doped microporous carbon-supported zinc-based catalyst used in the following example is as follows: 3g chitosan and 6g zinc chloride are dissolved in 100mL 10wt% acetic acid aqueous solution and stirred at room temperature to form a uniform translucent paste solution. The solution is poured into a petri dish and dried in an oven at 80°C overnight to obtain a dry solid. The solid is ground into powder and then calcined in a N2 atmosphere at the target temperature (900°C) for more than 2 hours (the heating rate from room temperature to 900°C is 3°C min-1). The black powder obtained by cooling to room temperature after calcination is the target catalyst Zn-NC, which can be used directly without further treatment. The mass content of Zn is 0.5wt%, the mass content of N is 1wt%, and the pore size range is 10-20nm.
[0023] The preparation method of the copper-based catalyst supported by nitrogen-doped microporous carbon used in the following example is as follows: 3 g of chitosan and 0.2 g of copper nitrate are dissolved in 100 mL of 10 wt% acetic acid aqueous solution and stirred at room temperature to form a uniform translucent paste solution. The solution is poured into a petri dish and placed in an oven at 80°C overnight to obtain a dry solid. The solid is ground into powder and then calcined in a N2 atmosphere at the target temperature (900°C) for more than 2 hours (the heating rate from room temperature to 900°C is 3°C min -1 ). After calcination and cooling to room temperature, the resulting black powder is the target catalyst Cu-NC, which can be used directly without further treatment. The mass content of Cu is 0.8wt%, the mass content of N is 1.2wt%, and the pore size range is 10-20nm.
[0024] The preparation method of the nitrogen-doped microporous carbon-supported cobalt-based catalyst used in the following example is as follows: 3g chitosan and 0.2g cobalt nitrate are dissolved in 100mL 10wt% acetic acid aqueous solution, and stirred at room temperature to form a uniform translucent paste solution. The solution is poured into a culture dish and dried in an oven at 80°C overnight to obtain a dry solid. The solid is ground into powder and then calcined in a N2 atmosphere at the target temperature (900°C) for more than 2 hours (the heating rate from room temperature to 900°C is 5°C min-1). The black powder obtained by cooling to room temperature after calcination is the target catalyst Co-NC, which can be used directly without further treatment. The mass content of Co is 0.6wt%, the mass content of N is 1.5wt%, and the pore size range is 10-20nm.
[0025] The preparation method of the nitrogen-doped microporous carbon-supported nickel-based catalyst used in the following example is as follows: 3 g of chitosan and 0.2 g of ferric nitrate are dissolved in 100 mL of 10 wt% acetic acid aqueous solution and stirred at room temperature to form a uniform translucent paste solution. The solution is poured into a petri dish and placed in an oven at 80°C overnight to obtain a dry solid. The solid is ground into powder and then calcined in a N2 atmosphere at the target temperature (900°C) for more than 2 hours (the heating rate from room temperature to 900°C is 3°C min -1 ). After calcination and cooling to room temperature, the resulting black powder is the target catalyst Fe-NC, which can be used directly without further treatment. The Fe mass content is 0.9wt%, the N mass content is 1.5wt%, and the pore size range is 10-20nm.
[0026] The preparation method of the nitrogen-doped microporous carbon-supported zinc-based catalyst (acid washing) used in the following example is as follows: 3 g of chitosan and 6 g of zinc chloride are dissolved in 100 mL of 10 wt% acetic acid aqueous solution and stirred at room temperature to form a uniform translucent paste solution. The solution is poured into a petri dish and placed in an oven at 80°C overnight to obtain a dry solid. The solid is ground into powder and then calcined in a N2 atmosphere at the target temperature (900°C) for more than 2 hours (the heating rate from room temperature to 900°C is 3°C min -1 After calcination, the black powder was cooled to room temperature, stirred with 10 mL of hydrochloric acid solution (1.0 mol / L) for more than 6 hours, then washed with deionized water until neutral, and dried in an oven at 80°C to obtain the target catalyst Zn-NC (acid washed). The mass content of Zn is 0.4 wt%, the mass content of N is 1.8 wt%, and the pore size range is 10-20 nm.
[0027] The preparation method of the nitrogen-doped microporous carbon-supported non-metallic catalyst used in the following example is as follows: 3 g of chitosan was dissolved in 100 mL of 10 wt% acetic acid aqueous solution and stirred at room temperature to form a uniform translucent paste solution. The solution was poured into a petri dish and dried in an oven at 80°C overnight to obtain a dry solid. The solid was ground into powder and then calcined in a N2 atmosphere at the target temperature (900°C) for more than 2 hours (the heating rate from room temperature to 900°C was 3°C min -1 The black powder obtained after calcination and cooling to room temperature is the target catalyst NC, which can be used directly without further treatment. The mass content of N is 2.1wt%, and the pore size range is 10-20nm.
[0028] Example 1
[0029] N-methylbenzylamine (0.25mmol), Zn-NC (relative to the raw material 5mol%, in terms of the molar number of Zn), NH3·H2O (1.0mmol) and 2mL DMSO were added to a 5mL reaction tube in sequence, sealed with a polytetrafluoroethylene plug with a through hole (aperture of 2mm), and then transferred to a stainless steel autoclave. The autoclave was filled with 1.0MPa of oxygen, emptied, and reciprocated oxygenation and emptied 3 times, and finally filled with oxygen pressure to 1.0MPa. The reactor was placed in a 150°C oil bath and stirred at 550rpm for 12h. After the reaction was completed, the reactor was cooled to room temperature, opened, and 20mg of internal standard naphthalene and 2mL of MeOH were added. After stirring evenly, the mixture was ultrasonicated and centrifuged. An appropriate amount of the clear liquid was taken and the qualitative product was detected by gas chromatography-mass spectrometry. The conversion rate of the quantitative substrate N-methylbenzylamine and the yield of the product benzonitrile by gas chromatography internal standard method are shown in Table 1.
[0030] Example 2-33.
[0031] Except for the catalyst and dosage, pressure and reaction time, the catalyst activity evaluation is the same as that in Example 1. The reaction conditions and catalytic reaction results are shown in Table 1. It can be seen from Table 1 that the catalyst and dosage, oxygen source type, oxygen pressure, ammonia source type, reaction temperature and reaction time have an effect on the catalytic effect. The amount and type of catalyst (Examples 1 and 2-9), the type of solvent (Examples 1 and 10-16), the amount and type of ammonia source (Examples 1 and 17-26) are different, and the catalytic effect is also different. With the increase of reaction temperature (Examples 1 and 27, 28), oxygen source type, pressure (Examples 1 and 29-31) and reaction time (Examples 1 and 32, 33), the yield increases.
[0032] Table 1 Preparation of organic nitrile by oxidative cleavage of N-methylbenzylamine
[0033]
[0034]
[0035] The amount of catalyst refers to the mol% of the raw material based on the metal; NC means that it has the same mass as metal-NC;
[0036] Examples 34-54
[0037] Except for the different substrates, the catalyst activity evaluation and reaction conditions were the same as those in Example 1, and the reaction time was 12-24 h. The substrates and catalytic reaction results are shown in Table 2. Nitrogen-containing substrates can all undergo oxidative cleavage of the carbon-nitrogen bond to generate corresponding organic nitrile compounds, indicating that this method has universal applicability.
[0038] Table 2 Oxidative cracking of nitrogen-containing compounds
[0039]
[0040]
[0041]
[0042] The invention has a wide substrate range, high oxidation efficiency, good selectivity and high product yield; oxygen is used as an oxygen source, which is environmentally friendly; the catalyst can be recycled, and the post-treatment is simple, and has a good application prospect.
Claims
1. A method for preparing nitrile compounds by cracking nitrogen-containing compounds, characterized in that: A nitrogen-containing compound, an ammonia source, a nitrogen-doped carbon-loaded zinc-based catalyst and a solvent are added to a reaction tube, which is then transferred to a high-pressure reactor, and an oxygen source gas of 0.2-2.0 MPa is introduced. The reactor is placed in an oil bath at 100-180°C for reaction for 4-50 hours, so that the carbon-nitrogen bond (CN) can be oxidatively broken to generate the corresponding nitrile compound.
2. According to the method of claim 1, the preparation process of the nitrogen-doped carbon-supported zinc-based catalyst is as follows: 2-5g chitosan (preferably 3-4g) and 4-8g zinc chloride (preferably 6-7g) are dissolved in 100mL 5-10wt% acetic acid aqueous solution, and stirred at room temperature to form a uniform paste solution; the solution is poured into a culture dish, and dried in an oven at 80-100°C to obtain a dry solid; the solid is ground into powder, and then calcined in a N2 atmosphere at a target temperature (800-1000°C) for more than 2 hours (the heating rate from room temperature to 800-1000°C is 2-5°C min -1 ); after calcination and cooling to room temperature, the resulting black powder is the target catalyst Zn-NC.
3. The method according to claim 1, characterized in that: The catalyst Zn-NC can be used directly without further treatment; the mass content of Zn is 0.5-2wt%, the mass content of N is 1-5wt%; and the pore size range is 10-20nm.
4. The method according to claim 1, characterized in that: The nitrogen-containing compound is a benzylamine compound In the benzylamine compound molecule, the substituent R on the benzene ring is one or more of phenyl, naphthyl, thiophene ring, pyridine ring, -CH3, -OCH3, -C(CH3)3, -F, -Cl, -Br, -CF3; or the benzene ring can be replaced by a naphthalene ring, a thiophene ring or a pyridine ring; In the compounds containing other substituents R on the benzene ring, the positions of the other substituents are para, meta or ortho; In the nitrogen-containing compound having other substituents on the benzene ring, the number of the other substituents is 1, 2, 3 or 4.
5. The method according to claim 1, characterized in that: The molar ratio of the amount of catalyst added to the amount of nitrogen-containing reaction substrate charged is 0.005-0.05, preferably 0.04-0.05, based on the molar number of Zn.
6. The method according to claim 1, characterized in that: The solvent is one or more of 1,4-dioxane, N,N-dimethylformamide (DMF), dimethyl sulfoxide (DMSO), 1,2-dichloroethane, toluene, acetonitrile, n-heptane, and methanol, and the amount used is 1-4 mL, preferably 2-3 mL, for every 0.25 mmol of the nitrogen-containing compound.
7. The method according to claim 1, characterized in that: The ammonia source is an alkaline inorganic compound, including one or more of ammonia water, ammonium carbonate, ammonium bicarbonate, ammonium oxalate, ammonium chloride, ammonium sulfate, and ammonium acetate; the molar ratio of the added amount of the ammonia source to the nitrogen-containing reaction substrate is 1-6, preferably 4-5.
8. The method according to claim 1, characterized in that: The oxygen source gas used is one or both of pure oxygen and air; the pressure of the oxygen source gas used is 0.2-2.0 MPa, preferably 1.0 MPa.
9. The method according to claim 1, characterized in that: The reaction temperature is 100-180° C., preferably 130-160° C.; the reaction time is 4-50 h, preferably 12-24 h.